Cointegration and Causality between Financial Development and Economic Growth: Evidence from Morocco - Chatri, Abdellatif; Maaruf, Abdelouahab (The Indonesian Capital Market Review, 2014)
The debate on the relationship between economic growth and financial development has been steadily growing in these recent years. However, the existing theoretical and empirical literature provides conflicting views in this respect. This Headline topic proposes an empirical investigation of the nature of this relationship in the Moroccan context. More precisely, it explores the cointegrating and the causality issue between economic growth and financial development. The later is measured by largely used indicators. In particular, we use capital market proxy, in addition to the traditional indicators of financial intermediation. The findings show that financial development explains significantly the growth, but the direction of causality depends on the indicator used to measure the financial deepening and the time horizon of analysis (short or long terms)